Cushites in the Hebrew Bible : negotiating ethnic identity in the past and present - Burrell, Kevin, 1979- (Biblical Interpretation Series;, 2020)
"Cushites in the Hebrew Bible offers a reassessment of Cushite ethnographic representations in the biblical literature as a counterpoint to misconceptions about Africa and people of African descent which are largely a feature of the modern age. Whereas current interpretations have tended to emphasize unfavourable portraits of the people biblical writers called Cushites, Kevin Burrell illuminates the biblical perspective through a comparative assessment of ancient and modern forms of identity construction. Past and present modes of defining difference betray both similarities and differences to ethnic representations in the Hebrew Bible, providing important contexts for understanding the biblical view. This book contributes to a clearer understanding of the theological, historical, and ethnic dynamics underpinning representations of Cushites in the Hebrew Bible"--Provided by publisher.